Unique photodynamic antimicrobial Schiff bases and their copper complexes exert immunomodulatory activity on mammalian macrophages. Issue 20 (29th October 2020) - Gonul, Ilyas; Demirbag, Burcu; Ocakoglu, Kasim; Ayaz, Furkan
Abstract: Antibiotic resistance has been a growing problem for the public health. Especially the hospitalized patients are at high risk due to emergence of superbugs that can evade a wide range of antibiotics in use. In order to circumvent this major problem, new candidates of antimicrobial agents should be created and tested for their efficacies. Moreover, having antimicrobial agents that could get activated with light exposure (antimicrobial PDT) would create a great advantage in terms of decreasing the required effective dose as well as controlled localized activation of the candidate drugs. Schiff base derivatives have antimicrobial, antitumor, and anti-inflammatory activities. In this study, we used a unique set of Schiff base derivatives with and without copper for antimicrobial PDT applications both on gram-negative Escherichia coli and gram-positive Staphylococcus aureus . Our compounds had strong antimicrobial PDT potential especially with the addition of copper into their structures. Moreover, these Schiff base derivatives' possible immunomodulatory activities were tested on mammalian macrophages in vitro . These compounds had photodynamic anti-inflammatory activities as well. Our results suggest that these unique Schiff bases can be utilized in antimicrobial PDT applications that can also alter the function of the immune system cells to suppress excessive inflammation. Graphical Abstract: